Pengaruh Penggunaan Aplikasi Google Classroom pada Pembelajaran Daring saat Pandemi Covid-19 terhadap Capaian Kognitif Pembelajaran Biologi Kelas X di SMAN 2 Gunung Talang - Annisa Adelina Fajri; Despryhati Ningsih (PAKAR Pendidikan, 2022)
The Google Classroom application is one of the applications commonly used in distance learning. During the Covid-19 Pandemic, the face-to-face learning process had to be replaced with learning from home, this was done to minimize the spread of Coronavirus which is the cause of Coronavirus Disease (Covid-19). This application, in addition to facilitating article sharing, can also be used to share learning video links and to carry out online exams, both in the form of objective and essay form. This research is an experimental research with Static Group Comparison design. This study aims to examine the effect of using the Google Classroom application on the cognitive achievement of class X MIPA students in Biology at SMAN 2 Gunung Talang in the 2020/2021 academic year. The instruments used in this study were 35 objective questions that had been validated by the MGMP Biology teachers of Kab. Solok and tested for reliability on 94 Class X MIPA students at SMAN 2 Gunung Talang for the 2019/2020 academic year. Data were analyzed using t-test with criteria if tcount > t table, the hypothesis was accepted, and vice versa. The results showed that the average value of students in the experimental class was found to be higher than the average value of students in the control class, and based on the results of the comparison of t values, it was found that the population data were normal, homogeneous, and the results of the hypothesis proved positive.